IMAGE OF EUROPE IN CONTEMPORARY SOUTH KOREAN TV SERIES: ART TERRITORY, FAIRY-TALE TERRITORY / ОБРАЗ ЕВРОПЫ В СОВРЕМЕННОМ ЮЖНОКОРЕЙСКОМ ТЕЛЕСЕРИАЛЕ: ТЕРРИТОРИЯ ИСКУССТВА, ТЕРРИТОРИЯ СКАЗКИ - TARASOVA ALEXANDRA V. / ТАРАСОВА А.В. (Наука телевидения)
This article explores how the image of Europe and the West in general is constructed in South Korean TV series. The undiminished interest of the global audience to series produced in the Republic of South Korea is combined with clearly discernible genre features and plot motifs imported from the West in these products, as well as quotes from and allusions to Western films and TV shows. This makes it particularly relevant to ask how the “European” can be distinguished in such a hybrid series narrative, what characteristics are assigned to it, and what techniques are used to describe it. This series of issues is inextricably linked to the problem of national identity, since, in identifying markers of otherness and analyzing the nature of interactions with the “Western”, we necessarily touch upon the system of ideas about the “Korean” transmitted by the creators of television series. The next step could be defining to what extent a television series reflects the views that already exist in the target audience, but that is beyond the scope of this research. This article focuses on The Package TV series which is mostly set in France. Analyzing individual parts that make up the image of France enables us to see where the significant differences between the “European” and the “Korean” lie and to establish the content of the narrative about the “European”. The results of this analysis support the discussion of the special place occupied by the discourse of the Western art and the discourse of the “fairy tale” in this Korean TV image of Europe. Examples from a number of other TV series that were broadcast around the same time as The Package confirm this observation.